PENINGKATAN MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MEDIA VISUAL DI KELAS 8 SMPN 11 BENGKULU TENGAH - Salamah, Salamah; Dekri Nopita Sari, Dekri Nopita Sari; Nur Adzim, Rahmad Hidayat; Avra, Errick; Faddillah.S, Yuni (Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to increase students' learning motivation in Islamic Religious Education (PAI) subjects through the use of visual media in class 8 of SMPN 11 Central Bengkulu. Visual media was chosen as a learning strategy to increase students' interest and involvement in the learning process. The research method used is classroom action research (PTK) which consists of two cycles. Data was collected through observation, interviews, questionnaires and documentation. The research results show that the use of visual media can significantly increase students' learning motivation. This is shown by increasing student activity in class discussions, increasing the average value of daily tests, and increasing positive responses to learning.